Creativity In Presenting Music With Audio Visual Media Through The Youtube Platform At The Orenji Music School Institution - Puspita, Vananda Dwi; Sekti, Retnayu Prastyanti (PT. Hafasy Dwi Nawasena, 2024)
Efforts to respond for continuing to learning during the Covid-19 period which is online face-to-face meets. One of the music course institutions that still survive despites being impacted by COVID-19 is Orenji’s Music School course. This research aims to describe the creativity of presenting music through audio-visual media by YouTube platform at the Orenji’s Music School institution. The theory that used in this research also addresses the Covid-19 condition through creativity and audio-visual media. The research method that used is a descriptive qualitative. The research data source uses primary data obtained directly from sources and informants, while secondary data is obtained not directly but from objects that observed via online YouTube media. Data collection techniques are carried out through online or verbal observation of objects, interviews and then documentations. Data analytic techniques are carried out through the stages of data reduction, data presentation, data verification. The validity of research data using triangulation techniques, namely from sources, techniques and time processes.